In search of an ideal template for therapeutic genome editing: A review of current developments for structure optimization - Shakirova, Alena; Karpov, Timofey; Komarova, Yaroslava; Lepik, Kirill (Frontiers in Genome Editing, 2023)
Gene therapy is an increasingly developing field of medicine with hundreds of ongoing early-stage clinical trials and numerous preclinical studies. Genome editing (GE) now is an increasingly important technology for stable therapeutic gene correction, with hematopoietic cells representing a key target population for development of novel treatments for a set of hereditary diseases, infections and cancer. By introducing double strand break in the defined locus of genomic DNA, the GE tools allow to knock-out the desired gene or knock-in therapeutic gene if provided with appropriate transgene template. Currently, the efficiency of methods for GE-mediated transgene knock-in is limited. Significant efforts were focused on the improvement of parameters and interactions of GE nuclease proteins. However, an increasing body of data suggests that optimal characteristics of transgene templates may play an important role in the knock-in mechanisms. While viral vectors with notable example of AAVs as a donor template carrier remain a mainstay in many preclinical trials, non-viral templates represent a promising alternative, including plasmid and linear dsDNA, long ssDNA templates, single and double-stranded ODNs. Furthermore, tuning of editing conditions for chosen template as well as its structure, length, sequence optimization, homology arm (HA) modifications may hold a key importance for achievement of high knock-in efficiency with favorable safety profile. This review outlines the current developments in optimization of templates for genome-editing mediated therapeutic gene correction.